ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF BUDGET REALIZATION TO ASSESS THE PERFORMANCE OF THE STATE TREASURY SERVICE OFFICE (KPPN) - Taliding, Arianto; Gemini, Pra; Nurmega; Askar, Muhammad (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to analyze the effectiveness and efficiency of budget realization as a basis for evaluating the performance of the State Treasury Service Office (KPPN) Makassar I for the period 2020 to 2024. The research uses a descriptive quantitative method with secondary data derived from budget realization reports and the number of Payment Order Letters (SP2D) issued to partner work units of KPPN Makassar I. Effectiveness is measured by the ratio of realization to budget allocation, while efficiency is measured by the ratio of realization to the number of SP2D issued. The results show that the effectiveness of budget realization over fire years consistently falls under the “effective” category, with ratios ranging from 93,98% to 97,04%. Meanwhile, efficiency fluctuated but showed significant improvement in the last two years, with the highest value of Rp. 210.523.391 per SP2D in 2023. These findings indicate that KPPN Makassar I has demonstrated good performance in budget disbursement. Therefore, the hypothesis stating that the effectiveness and efficiency of budget realization at KPPN Makassar I meet good criteria is accepted.